1995
DOI: 10.1007/bf01690260
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene enhances shoot formation in cultures of the peach rootstock GF-677 (Prunus persica x P. amygdalus)

Abstract: The influence of ethylene on shoot formation from GF-677 (Prunus persica × P. amygdalus) shoot tip explants was studied in vitro. Cultures in test tubes were placed inside 5 1 glass jars and supplemented with various ethylene concentrations (0-10 ppm). Ethylene at 0.1 ppm, applied during the first 2 weeks of culture, increased the number and the length of shoots produced in vitro. Test tubes with cultures sealed with various types of closure accumulated in their atmosphere different levels of ethylene ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…An increase in the number of secondary shoots arising from explants of 'Little Pinkie' when exposed to approximately 60 nL L −1 ethylene, is consistent with a promotional effect of 100 nL L −1 on shoot formation of peach (Dimasi-Theriou and Economou, 1995), and that of slightly higher concentrations of 1000 and 1280 nL L −1 on multiplication rate of rose (Kevers et al, 1992) and eastern white cedar (Nour and Thorpe, 1994) explants in vitro. While in contrast, application of a very high concentration of ethylene (10,000 nL L −1 ) suppressed the number of shoots in peach, a low concentration (100 nL L −1 ) increased it (Dimasi-Theriou and Economou, 1995).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…An increase in the number of secondary shoots arising from explants of 'Little Pinkie' when exposed to approximately 60 nL L −1 ethylene, is consistent with a promotional effect of 100 nL L −1 on shoot formation of peach (Dimasi-Theriou and Economou, 1995), and that of slightly higher concentrations of 1000 and 1280 nL L −1 on multiplication rate of rose (Kevers et al, 1992) and eastern white cedar (Nour and Thorpe, 1994) explants in vitro. While in contrast, application of a very high concentration of ethylene (10,000 nL L −1 ) suppressed the number of shoots in peach, a low concentration (100 nL L −1 ) increased it (Dimasi-Theriou and Economou, 1995).…”
Section: Discussionsupporting
confidence: 75%
“…While in contrast, application of a very high concentration of ethylene (10,000 nL L −1 ) suppressed the number of shoots in peach, a low concentration (100 nL L −1 ) increased it (Dimasi-Theriou and Economou, 1995). The results of the aforementioned studies, as well as the result of the current study, therefore support the hypothesis that low concentrations of ethylene in ventilated systems, within a range of 60-1280 nL L −1 , can encourage the growth and development of branches in explants whereas high concentrations (10,000 nL L −1 ) may be inhibitory, especially in sealed vessels where altered levels of other gases (e.g.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have already reported that STS and similar compounds, like silver nitrate, are biologically active at very low concentrations for some plant species [34,36]; in these cases, if the maximum effective concentration of STS is reached, toxic effects on plant tissues are induced and regeneration responses are inhibited, as also observed in our study. This also suggests that, at the right level, the presence of ethylene in the tissue culture is still needed for an efficient organogenetic response, as also reported by other studies [37,38]. Thus, as remarked by Petri and Scorza [18], the optimum STS concentration in Prunus spp.…”
Section: Discussionsupporting
confidence: 71%
“…Callus formation can also be infl uenced by the level of ethylene (Biddington, 1992). It has also been reported that ethylene enhances shoot and root formation in some species, such as petunia (Dimasi-Theriou et al, 1993) and peach rootstock (Dimasi-Theriou and Economou, 1995). Nevertheless, there are also many crops extremely susceptible to ethyleneinduced in vitro.…”
Section: Discussionmentioning
confidence: 99%